Effects of zero defects approach-a case study at an Indian industry - Karunakaran, K; Saravanan, R; Venkumar, P; Sridha, R (International Journal of Engineering and Technology, 2018)
Quality is free when reaches zero defects, quality is measured various aspects. The rework is carried out when the product finish not up to the standard, which added additional expenditure. On other side if there is no chance for rework the cost of raw material and value added cost up to that non conformity is lost. This work shares a success story and reveals a systematic scientific approach to reach zero defects. The case study conducted in the leading supplier who focuses on climate and energy efficient solutions. The traditional powerful quality tools employed to focus, understanding and analyse the problem. The Decision support system preferred and adopted to solve the problem with affordable cost. The outcomes of this work measured in terms of modern Total Productive Maintenance style that is in terms of Productivity, Quality, Cost, Delivery, Safety, Motivation and Morale (PQCDSM). The results in all the way found more significant.Â